LATE VENTRICULAR POTENTIALS AND CARDIAC ARRHYTHMIAS IN PATIENTS WITH CARDIAC CONNECTIVE TISSUE DYSPLASIA AND ARTERIAL HYPERTENSION - E. Yu. Isakova; O. N. Ragozin (Российский кардиологический журнал)
To investigate the association between late ventricular potentials and cardiac arrhythmias, 35 patients with cardiac connective tissue dysplasia (CTD), 34 patients with cardiac CTD and arterial hypertension (AH), and 39 relatively healthy people were examined. All participants underwent 24-hour ECG monitoring, echocardiography, and high definition ECG, in accordance with the 1999 clinical guidelines by the European Society of Cardiology. The duration of filtered QRS signal and low-amplitude signals at 40 mkV level in the end of QRS, as well as mean quadratic amplitude of the last 40 ms of filtered QRS signal, were assessed. High definition ECG and Holter ECG monitoring facilitates the prediction of life-threatening ventricular arrhythmias in patients with cardiac CTD.